IDENTIFICATION LINGUISTICS AS AN ASPECT OF LINGVOPERSONOLOGY - G. V. Napreenko (Вестник Кемеровского государственного университета, 2015)
The paper presents an aspect of lingvopersonology called “identification linguistics”. Identification linguistics originates from the universal phenomenon of identification, based on the establishment of the identity of objects, and is implemented in lingvopersonology (identification of linguistic identity) and legal linguistics (linguistic identification expertise). The requirement of objectivity and reliability of the identification output affects the emergence of a large number of authentication methods, which are presented in the opposition of specially-oriented and generic methods.